2011
DOI: 10.1631/jzus.b1000439
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft noise exposure affects rat behavior, plasma norepinephrine levels, and cell morphology of the temporal lobe

Abstract: Abstract:In order to investigate the physiological effects of airport noise exposure on organisms, in this study, we exposed Sprague-Dawley rats in soundproof chambers to previously recorded aircraft-related noise for 65 d. For comparison, we also used unexposed control rats. Noise was arranged according to aircraft flight schedules and was adjusted to its weighted equivalent continuous perceived noise levels (L WECPN ) of 75 and 80 dB for the two experimental groups. We examined rat behaviors through an open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The results of the current work show that rats exposed to acute or chronic noise have significantly elevated plasma levels of corticosterone, adrenaline and noradrenaline as compared to the control rats unexposed to noise and this elevation is significantly higher in chronic continuous stress group as compared with both acute or chronic intermittent stress groups. These findings are congruent to the previous studies which concluded that rats exposed to noise showed elevated plasma levels of corticosterone (Soldani et al 1999;Samson et al 2007;Gannouni et al 2013), adrenaline and noradrenaline (Maschke et al 2002;Lenzi et al 2003;Maschke 2003;Di et al 2011;Schmidt et al 2013). These endocrinal changes in response to exposure to noise stress can be explained by activation of autonomic nervous system (Turner et al 2005) or structural and functional modifications occurring in the adrenal cortex and medulla which are supposed to be mediated by increased free oxygen radicals (Soldani et al 1999;Kanitz et 115.56 Data is expressed as mean ± standard deviation (n = 8 per group).…”
Section: Discussionsupporting
confidence: 92%
“…The results of the current work show that rats exposed to acute or chronic noise have significantly elevated plasma levels of corticosterone, adrenaline and noradrenaline as compared to the control rats unexposed to noise and this elevation is significantly higher in chronic continuous stress group as compared with both acute or chronic intermittent stress groups. These findings are congruent to the previous studies which concluded that rats exposed to noise showed elevated plasma levels of corticosterone (Soldani et al 1999;Samson et al 2007;Gannouni et al 2013), adrenaline and noradrenaline (Maschke et al 2002;Lenzi et al 2003;Maschke 2003;Di et al 2011;Schmidt et al 2013). These endocrinal changes in response to exposure to noise stress can be explained by activation of autonomic nervous system (Turner et al 2005) or structural and functional modifications occurring in the adrenal cortex and medulla which are supposed to be mediated by increased free oxygen radicals (Soldani et al 1999;Kanitz et 115.56 Data is expressed as mean ± standard deviation (n = 8 per group).…”
Section: Discussionsupporting
confidence: 92%
“…This function can be the same in sleep-deprived rats and sleep-restricted rats (32). NE is one of the stress hormones used as an indicator of stressful situations in the body and this hormone plays an important role in adapting to stress (40)(41)(42). Plasma NE level depends on the activity rate of the sympathetic nervous system (43).…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported that anxiety and depression are considerably related to increased NE levels in blood plasma (40,43). Patients with depression disorder show increases in plasma NE concentration in different conditions (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Past experiments have applied various types of noise to induce stress, such as traffic noise (Jafari et al., 2018; Kim et al., 2017), high‐speed railway sounds (Di & Zheng, 2013), aircraft noise (G. D. Di et al., 2011), white noise (Cui et al., 2009; Pascuan et al., 2014; Ravindran et al., 2005), a screaming sound (Hu et al., 2014), and pure‐tones (Jafari et al, 2019b; Jafari, Mehla, et al, 2019; Mazurek et al., 2010). This variability in noise stress paradigms results from the fact that noise annoyance, the major impact of noise on brain function, is a non‐acoustical phenomenon, irrespective of the physical characteristics of the noise (Fields, 1993; Stallen, 1999).…”
Section: Methodsmentioning
confidence: 99%